2020
DOI: 10.3390/su122310206
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Determinants of Sport Expenditure in Sports Centers in Spain

Abstract: The sports center sector is undergoing a complete transformation. Knowing users’ behavior regarding sport expenditure is needed to be able to act in terms of the future of the sector. This study analyzes the expenditure of people in Spain who are members of sports centers. Adult members were asked about their sport expenditure in several defined categories. An analysis of variance (ANOVA) and a multiple logistic regression analysis were carried out. The results show that the variables of time of participation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Research has indicated that consumers also develop brand identification, or allegiance to brands, based on their positive perception of their CSR activities [69,70]. Consumer perception determines the value of certain CSR activities from a consumer's perspective, so several researchers have taken perception to be central to such studies [23,71,72]. Researchers have found that consumers develop brand identification with the brands that deliver a CSR message.…”
Section: Spectators' Perceptions Of Corporate Social Responsibility (...mentioning
confidence: 99%
“…Research has indicated that consumers also develop brand identification, or allegiance to brands, based on their positive perception of their CSR activities [69,70]. Consumer perception determines the value of certain CSR activities from a consumer's perspective, so several researchers have taken perception to be central to such studies [23,71,72]. Researchers have found that consumers develop brand identification with the brands that deliver a CSR message.…”
Section: Spectators' Perceptions Of Corporate Social Responsibility (...mentioning
confidence: 99%
“…There was also a favourable association. The variables of period of participation, federation membership, and income have anticipating value in terms of sport expenditure, according to Elasri-Ejjaberi et al [ 99 ]. Age and educational level also contribute to the stark variations in sport spending across its major categories.…”
Section: Discussionmentioning
confidence: 99%
“…Though there has been significant growth in sponsorship research in the last decade by employing various theories and frameworks to unearth how consumers respond to a sponsorship effect on their purchase intention and behavior (Seung-Hoon et al, 2019; Melovic et al, 2019;Trivedi, 2020;Elasri Ejjaberi et al, 2020;Pan and Phua, 2021), prior studies have drawbacks which require urgent attention. Firstly, existing studies of sponsorship research are dominantly focused on developed economies, with very little effort in emerging economies like Ghana.…”
Section: Introductionmentioning
confidence: 99%